Lactobacillus casei CCFM1074 Alleviates Collagen-Induced Arthritis in Rats via Balancing Treg/Th17 and Modulating the Metabolites and Gut Microbiota - Fan, Zhexin; Ross, R. Paul; Stanton, Catherine; Hou, Bao; Zhao, Jianxin; Zhang, Hao; Yang, Bo; Chen, Wei (Frontiers in Immunology, 2021)
Gut microbiota and their influence on metabolites are receiving increasing attentions in autoimmune diseases including rheumatoid arthritis (RA). Probiotics become a promising manipulator to prevent or attenuate the progression of arthritis, some evidences suggesting that lactobacilli treatment influence the responses to RA therapy but the underlying mechanisms are limited. By using a collagen-induced arthritis (CIA) rats, the study assessed the effects of two L. casei strains (CCFM1074, CCFM1075) on the immune responses, gut microbiota and plasma metabolites via an integrated cross-omics approach including fecal 16S rRNA high-throughput sequencing and plasma metabolomics. The genome of the two strains was analyzed and compared using whole-genome sequencing approach to further confirm biology functions. CCFM1074 reduced arthritic symptoms while CCFM1075 did not, though both strains down-regulated the plasma IL-6 and Th17 cells proportion. CCFM1074 enhanced the proportion of Treg cells in mesenteric lymph nodes which was significantly associated with SCFAs upregulation, as well as with genomic evidence that CCFM1074 possesses more functional genes involved in carbohydrate metabolism. Moreover, CCFM1074 regulated the gut microbiota, including modulating community structure, decreasing the abundance of Alistipes and Parabacteroides and increasing the abundance of Oscillibacter. The differential metabolites modulated by CCFM1074 including eicosapentaenoic acid and docosapentaenoic acid which involved in unsaturated fatty acids metabolism. Furthermore, alterations of gut microbial community were correlated with the plasma metabolome. In summary, L. casei CCFM1074 alleviated arthritis via rebalancing gut microbiota, immune responses and plasma metabolites.